Self-inflicted powered knife penetrating neck injury - A case report - Miguel Carvalho; Márcia Mourão; Miguel Silva; Sérgio Raposo (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Laryngeal fractures are a rare event. Penetrating neck injuries produced by powered tools can be life-threatening and pose a challenge for head and neck surgeons. We report the case of a 51-year-old male that attempted suicide by self-inflicting a penetrating anterior neck injury with a powered knife. Neck exploration revealed section of all infrahyoid muscles exposing the carotid artery bilaterally, multiple laryngeal fractures, hypopharyngeal and esophageal lacerations. We classified the penetrating injury as a Schaefer-Fuhrman group 4. Reconstruction of the hypopharynx, esophagus and strap muscles was done with absorbable sutures. Reconstruction of the thyroid cartilage was performed with non-absorbable sutures. Post-operative evaluation revealed structural integrity of the hypopharynx and esophagus, as well as bilateral vocal fold mobility 6 months after the surgery. To improve patient survival and outcome, it’s of utmost importance that head and neck surgeons have a comprehensive understanding of the management of these unusual type of injuries.